The Initial Impact of the Open Scholarship Policy Observatory - Milligan, Sarah; Silk, Kimberly; Arbuckle, Alyssa; Siemens, Ray (KULA)

(untitled) (University of Victoria Libraries, 2019)
In September 2016, members of the Implementing New Knowledge Environments (INKE) Partnership—a broad, diverse group working to advance understanding of, and resolve critical issues in, the production, distribution and widespread engagement of digital scholarship in Canada and beyond—met to discuss future directions and focus areas. One of the resulting initiatives is the Open Scholarship Policy Observatory. The Open Scholarship Policy Observatory tracks national and international policies and policy changes in order to assist INKE partners with developing timely and responsive policies. This paper describes the development of the initiative, and reports on the initial impacts the project has had to date.